Incidence of acute intestinal infections in Saint Petersburg during COVID-19 pandemic - T. V. Potapova; K. D. Ermolenko; A. V. Kholin; A. V. Stalevskaya; S. A. Gordeeva; I. V. Razdyakonova (Журнал инфектологии)
The results of a study of modern epidemiological and characteristics of acute intestinal infections against the backdrop of the COVID-19 pandemic are presented. The article reflects current trends in the frequency of detection of acute intestinal infections of viral and bacterial etiology, in particular, the growing prevalence of norovirus infection is shown. Particular attention is paid to the increase in the incidence of salmonellosis and campylobacteriosis. An increase in the incidence of salmonellosis in 2019 by 25.7% is shown, which is higher than the average long-term incidence rate by 28.1%. Age features of the incidence of viral and bacterial intestinal infections among children have been established. Given the widespread use of antibiotics or other drugs that change the intestinal microbial landscape (cytostatics, chemotherapy drugs), as well as a significant increase in the number of hospitalizations of patients, there is a high risk of developing antibiotic-associated diarrhea. Undoubted attention requires the problem of registration, diagnosis of clostridium infections, which make it difficult to obtain data on the prevalence of infection caused by Clostridium difficile in the Russian Federation and St. Petersburg. The article discusses in detail the possibilities for further improvement of measures to prevent the transmission of acute intestinal infections.